11
$\begingroup$

I have a question concerning a statement about Random Walks on $\mathbb{Z}$. Let $F$ be a distribution on $\mathbb{Z}$ which has mean $0$ and finite variance. Let $\left\{X_1,X_2,\ldots\right\}$ be an i.i.d. sequence of random variables with distribution $F$.

Now there is the following statement:

$$ \text{Prob}\left\{S_1>0,S_2>0,\ldots,S_n>0\right\}\sim\sigma((2\pi n)^{1/2} E(S_N))^{-1}, $$ where $\sigma$ is the standard deviation of the distribution $F$, $N$ is the stopping time corresponding to the first entrance into $\left\{1,2,\ldots\right\}$ and $E$ denotes expected value.

For the proof, it is said, that the following four Theorems have to be combined. I tried a lot. I think one can start with (7.14) on page 415 (and maybe prove that statement afterwards), saying that (see notation below) $$ \frac{1-\tau(s)}{1-s}\sim \frac{e^{-c}}{\sqrt{1-s}}, s\to 1-. $$ The next step probably is to apply Theorems 2, 3, 4. But I am not sure how to do that exactly. Maybe you can help me.

--

Some notation before I give the Theorems.

Let $\mathfrak{T}_1$ be the epoch of the first entry into the (strictly) positive half-axis defined by $$ \left\{\mathfrak{T}_1=n\right\}=\left\{S_1\leq 0,\ldots,S_{n-1}\leq 0, S_n >0\right\}. $$ Let $\tau_n:=\mathbb{P}(\left\{S_1\leq 0,\ldots,S_{n-1}\leq 0, S_n >0\right\})$ and let $\tau(s)=\sum_{n=1}^{\infty}\tau_n s^n,~~0\leq s\leq 1$ be the generating function of $\mathfrak{T}_1$.

A positive function $L$ is said to vary slowly at infinity if for every fixed $x$, $\frac{L(tx)}{L(x)}\to 1, t\to\infty$.


Theorem 1 $$ \mathbb{P}\left\{\mathfrak{T}_1 > n\right\}\sim\frac{1}{\sqrt{\pi}}e^{-c}\frac{1}{\sqrt{n}},~~~c:=\sum_{n=1}^{\infty}\frac{1}{n} [\mathbb{P}\left\{S_n > 0\right\}-\frac{1}{2}]. $$


Theorem 2

The generating function of the probabilities $$ p_n=\mathbb{P}\left\{S_1 >0, S_2 >0,\ldots,S_n >0\right\} $$ is given by $$ p(s)=\frac{1}{1-\tau(s)}. $$ That is $$ \log p(s)=\sum_{n=1}^{\infty}\frac{s^n}{n}\mathbb{P}\left\{S_n>0\right\}. $$


Theorem 3

Let $q_n\geq 0$ and suppose that $$ Q(s)=\sum_{n=0}^{\infty}q_n s^n $$ converges for $0\leq s <1$. If $L$ varies slowly at infinity and $0\leq p <\infty$, then each of the two relations $$ Q(s)\sim\frac{1}{(1-s)^p}L\left(\frac{1}{1-s}\right), s\to 1-~~~(*) $$ and $$ q_0+q_1+\ldots+q_{n-1}\sim\frac{1}{\Gamma(p+1)}n^p L(n), n\to\infty $$ implies the other. Furthermore, if the sequence $\left\{q_n\right\}$ is monotonic and $0<p<\infty$, then $(*)$ is equivalent to $$ q_n\sim\frac{1}{\Gamma(p)}n^{p-1}L(n), n\to\infty. $$


Theorem 4

If $F$ has zero expectation and variance $\sigma^2$ the series $$ \sum_{n=1}^{\infty}\frac{1}{n} [\mathbb{P}\left\{S_n>0\right\}-\frac{1}{2}]=c $$ converges at least conditionally, and $$ \mathbb{E}(S_N)=\frac{\sigma}{\sqrt{2}}e^{-c}. $$


The Theorems are out of Feller, An Introduction to Probability Theory and its Applications which you may see here.

$\endgroup$
  • 1
    $\begingroup$ Is your main question (how to combine the four theorems to get the statement) in Feller's book also ? At which page ? $\endgroup$ – Ewan Delanoy Jun 21 '15 at 16:13
4
+500
$\begingroup$

Let $Q(s) = \frac{1-\tau(s)}{1-s}$. It is not hard to check that the coefficient $q_n$ of $s^n$ in $Q(s)$ is $$ q_n = 1-\sum_{m=0}^n \tau_m = \Pr[\mathfrak{T}_1 > n] \sim \frac{1}{\sqrt{\pi}} e^{-c} \frac{1}{\sqrt{n}}, $$ using Theorem 1. Clearly $q_n$ is monotonic. Taking $p = 1/2$ and using $\Gamma(1/2) = \sqrt{\pi}$, this shows that $$ q_n \sim \frac{1}{\Gamma(\pi)} n^{p-1} L(n), \qquad L(n) = e^{-c}. $$ Clearly $L(n)$ is slowly varying at infinity (it is constant), so Theorem 3 shows that as $s \to 1-$, $$ \frac{1-\tau(s)}{1-s} \sim \frac{e^{-c}}{\sqrt{1-s}}. $$ Theorem 2 implies that as $s \to 1-$, $$ p(s) = \frac{1}{1-s} \frac{1-s}{1-\tau(s)} \sim \frac{e^c}{\sqrt{1-s}}. $$ Applying Theorem 3 again for $p(s)$, $p=1/2$ and $L(n) = e^c$ (clearly $p_n$ is monotonic), we deduce that $$ p_n \sim \frac{1}{\sqrt{\pi}} n^{-1/2} e^c. $$

Theorem 4 implies that $$ p_n \sim \frac{\sigma}{\sqrt{2\pi}} n^{-1/2} \mathbb{E}(S_N)^{-1} = \sigma ((2\pi n)^{1/2} \mathbb{E}(S_N))^{-1}, $$ which is your statement.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.